2017 Pintó Sodoma - Escándalo de un mundo equivocado - - Grupo Teatro La Cochera (2017)
En escena: Adriana Audenino, Andrea Asis, Natalia Buyatti, María Belén Carranza Bertarelli, Florencia Cisnero, Daniela Ferreyra, Viviana Grandinetti, Pablo Huespe, Paula Lombardelli, Nahuel Maldonado, Agustín Malvarez, Claudia Peralta, Alejandro Pillado, Belén Salerno, Leticia Woods y Guillermo Wright | Dirección: Paco Giménez | Diseño gráfico: Karina Albiero | Fotografía: Andrea Asís / Juan Manuel Alonso | Diseño lumínico: Pablo Huespe | Equipo de Producción y Comunicación: Andrea Asis, Natalia Buyatti, Florencia Cisnero, Pablo Huespe y Belén Salerno. | Consultado el 7 de julio de 2017 | http://teatrolacochera.blogspot.com.ar/2017/05/estreno-pinto-sodoma-sabados-junio-22hs.html